Rancang Bangun Penyusunan Laporan Keuangan Berbasis Excel Pada PT Raksaka Teknologi Indonesia - Etna Liana; Hariadi Yutanto; Ellen Theresia Sihotang; Reza Tianto (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The object of this research is PT Raksaka Teknologi Indonesia, a company engaged in the IT sector, having its address at Jalan girlfriend No. 2A, Ketabang, Jl. Gayungsari Timur No.16 (MGI-2) Genteeng District, Surabaya. The purpose of this study was to determine the existing transaction recording system at PT Raksaka Teknologi Indonesia and to design the preparation of the financial statements of PT Raksaka Teknologi Indonesia using Microsoft Excel for Accounting. The research design used is a system design method with research data sources using primary data. At PT Raksaka Teknologi Indonesia, it is in recording transactions using Microsoft Excel which only has a general journal input worksheet. So that the design of the preparation of financial statements using Excel for Accounting (EFA) is the right solution in the constraints faced by the company. It is expected that PT Raksaka Teknologi Indonesia can implement accounting applications designed for business activities in businesses. Excel for accounting (EFA) which is designed as simple as possible and can be understood by employees of PT Raksaka Teknologi Indonesia.